Koperasi Waja and its Subsidiary Maju Jaya Sdn Bhd - Husain, Basrun (1997)

(untitled)
Koperasi Waja which was formally a credit and investment cooperative society, diversified its activities to venture into other economic activities that would benefit its members. Maju Jaya Sdn Bhd, a trading company was established in January 1980 as a subsidiary to Koperasi Waja. In it's earlier years, Maju Jaya generated good profit through it's trading activities, however in 1994, the company was no longer a profitable company. It experienced losses for the last 3 years. The management was in the process of reviewing the company as well as Koperasi Waja's present position and performance. The management would like to develop the organization as one of the competitive and dynamic Koperasi in this country.